2004
DOI: 10.1586/14760584.3.4.433
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness studies of pneumococcal conjugate vaccines

Abstract: The 7-valent pneumococcal conjugate vaccine is licensed in many countries for the prevention of pediatric pneumococcal disease. The vaccine is known to be highly immunogenic in infants and young children, and has been shown to be efficacious not only in decreasing disease in pediatric age groups but also in adults through herd immunity. Cost-effectiveness analyses of this vaccine have been performed in a number of countries. The present review compiles, summarizes and critiques these analyses. The range of val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…A number of other cost-effectiveness studies have evaluated the conjugate vaccine in North America, Europe and Australia, and a recent review reported that the cost per life year gained estimated in these studies is in the range of US $14,000-$147,000, with one outlier at US $504,000 [12]. Our base analysis excluding herd immunity falls within this range.…”
Section: Discussionmentioning
confidence: 72%
“…A number of other cost-effectiveness studies have evaluated the conjugate vaccine in North America, Europe and Australia, and a recent review reported that the cost per life year gained estimated in these studies is in the range of US $14,000-$147,000, with one outlier at US $504,000 [12]. Our base analysis excluding herd immunity falls within this range.…”
Section: Discussionmentioning
confidence: 72%
“…Moreover, results from cost-effectiveness analyses showed that indirect effects such as herd immunity and serotype replacement may have a crucial impact on the economic acceptability of alternative programs. 33,34 The serotype diversity of S. pneumoniae and its many clinical manifestations make it hard to answer questions related to the short as well as long-term effects that vaccination may have at the population level. Here, we have attempted to give some baseline information on the epidemiology of both invasive and non-invasive pneumococcal condition and on the potential impact of the available pneumococcal vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…In Western Europe, it is estimated that every child experiences one or more episodes of otitis media before the age of 2 years [7,8]. A number of studies have assessed the potential economical impact of mass infant vaccination with PCV7 (Prevnar; Wyeth) [9][10][11][12], since the first published clinical trial showed the high efficacy of this vaccine in the prevention of IPD [13] (see also McIntosh [14] for a recent review). Additionally, ongoing research has provided important new data.…”
Section: Introductionmentioning
confidence: 99%